Socio-economic determinants of pastoralists’ choice of camel production in Karamoja sub-region, Uganda - Biira Salamula, Jenipher; Egeru, Anthony; Asiimwe, Robert; Knox Aleper, Daniel; Jjumba Namaalwa, Justine (Pastoralism, 2017)
Camel production is a potential avenue for improved food and income security in dryland areas of East Africa. Despite this potential, there is a dearth of information on the increasing choice of camel production among pastoralists in the region. Camel-owning households were obtained through snowball sampling approach whereas those without camels were obtained randomly in the vicinity of those who had camels. A total of 116 respondents were interviewed in Moroto and Amudat districts of the Karamoja sub-region, Uganda. Descriptive statistics and binary probit regression analysis were conducted on the data. Results showed that 45% of the sampled households owned camels with an average camel holding of 17.96 ± 22.12 heads. There were more cows (9.67 ± 12.368) than bulls (3.85 ± 7.149) in the camel herds. Only 8% and 26% of camel herders had access to extension services and financial credit respectively. The binary probit regression model revealed that age of the household head, household size, on- farm income and herd size significantly influenced the decision to undertake camel production in the region. Furthermore, all the household members were engaged in different camel management activities; however, herding was mainly the responsibility of the children (34.9%) and adult males (32.1%). Milking was mainly done by women (33.6%) while disease management was done by adult males (48.7%) and the elderly (22%) in the household. Provision of higher milk quantities (44.3%) and camels being in the lineage (13.6%) were cited as the key motivations for camel rearing. On the other hand, 56% of respondents observed that the initial high cost of camel acquisition was the main limitation to owning camels. This study has shown that decision-making in transitioning to camel production in Karamoja is a result of socio-economic attributes including pastoralists’ perceptions of associated costs and benefits arising from camel production. Therefore, it is vital to strengthen innovative financing mechanisms and traditional systems such as agistments that can support pastoralists willing to acquire camels. There is need for extension services that target camel rearing where women and children are involved given their central role in camel management.
Keywords: Camels; Determinants; Pastoral; Resilience; Semi-arid